Дослідження впливу процесу кавітації на якість нафтових дистилятів - Лаврова, Інна Олегівна; Колеснікова, А. В.; Саід, Аммар В. (НТУ "ХПІ", 2011)
The article deals with issues related to the investigation of the influence of Ka-gravitational treatment on quality indicators of petroleum products. The experimental data have confirmed that cavitation treatment makes it possible to increase the yield of light fractions of petroleum, to reduce the content of oil products of total sulfur and mineral salts.
Keywords: нафта; нафтопереробка; кавітація; дистиляти